Large-scale mutagenesis of the mouse to understand the genetic bases of nervous system structure and function - Goldowitz, Dan; Frankel, Wayne N.; Takahashi, Joseph S.; Holtz-Vitaterna, Martha; Bult, Carol; Kibbe, Warren A.; Snoddy, Jay; Li, Yanxia; Pretel, Stephanie; Yates, Jeana; Swanson, Douglas J. (Brain research. Molecular brain research., 2004)
N-ethyl- N-nitrosourea (ENU) mutagenesis is presented as a powerful approach to developing models for human disease. The efforts of three NIH Mutagenesis Centers established for the detection of neuroscience-related phenotypes are described. Each center has developed an extensive panel of phenotype screens that assess nervous system structure and function. In particular, these screens focus on complex behavioral traits from drug and alcohol responses to circadian rhythms to epilepsy. Each of these centers has developed a bioinformatics infrastructure to track the extensive number of transactions that are inherent in these large-scale projects. Over 100 new mouse mutant lines have been defined through the efforts of these three mutagenesis centers and are presented to the research community via the centralized Web presence of the Neuromice.org consortium ( http://www.neuromice.org). This community resource provides visitors with the ability to search for specific mutant phenotypes, to view the genetic and phenotypic details of mutant mouse lines, and to order these mice for use in their own research program.